2020
DOI: 10.1007/s00281-020-00783-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic crosstalk in chronic infection with HIV-1

Abstract: Human immunodeficiency virus 1 (HIV-1) replicates through the integration of its viral DNA into the genome of human immune target cells. Chronically infected individuals thus carry a genomic burden of virus-derived sequences that persists through antiretroviral therapy. This burden consists of a small fraction of intact, but transcriptionally silenced, i.e. latent, viral genomes and a dominant fraction of defective sequences. Remarkably, all viral-derived sequences are subject to interaction with host cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 149 publications
(223 reference statements)
0
29
0
Order By: Relevance
“…Currently, no antiretroviral drugs inhibit basal transcription of provirus and blocks reactivation upon therapy (ART) interruption. It has been suggested that epigenetic silencing will be an important pre-requisite for persistent latency (81,82). Our expression and ChIP-qPCR data suggest that H2S could exert its influence on HIV replication machinery via activating YY1-an epigenetic silencer of HIV-1 LTR (56,68).…”
Section: Discussionmentioning
confidence: 66%
“…Currently, no antiretroviral drugs inhibit basal transcription of provirus and blocks reactivation upon therapy (ART) interruption. It has been suggested that epigenetic silencing will be an important pre-requisite for persistent latency (81,82). Our expression and ChIP-qPCR data suggest that H2S could exert its influence on HIV replication machinery via activating YY1-an epigenetic silencer of HIV-1 LTR (56,68).…”
Section: Discussionmentioning
confidence: 66%
“…With an exciting recent work showing that viral cell-to-cell transmission primes T cells to latent HIV-1 infections [ 169 ], another important challenge will be to determine how the repressive epigenetic status of the HIV-1 promoter is established in the early stages of the infection. This will provide further insights into the interplay between the epigenetic control of the virus and epigenetic alterations in the host, which might have fundamental consequences for HIV-1 clinical management [ 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…A role in the maintenance of viral latency was also reported for a genome-length antisense transcript devoid of poly-A tail (Transcript IV; Figure 3 ), which was detected in two chronically infected T-cell lines ( Saayman et al, 2014 ). In these cells, Transcript IV behaved as a long non-coding (lnc) RNA by recruiting chromatin modifying enzymes, such as DNA methyltransferase 3a (DNMT3a), Enhancer of Zeste Homolog 2 (EZH2), and Histone Deacetylase (HDAC)-1, to the 5' LTR of the provirus ( Saayman et al, 2014 ; Lange et al, 2020 ). This multiplicity of antisense transcripts characterized in vitro may be explained by the use of different methodological approaches in different studies.…”
Section: The Antisense Transcriptional Activity Of Hiv-1mentioning
confidence: 99%